"If I don’t enjoy it, how are my kids going to enjoy it?" : case study in English grammar teaching - Tewelde Habte, Yohana (2015)
The question over how grammar should be taught has been discussed amongst s everal linguistics scholars. Different grammar teaching methods present different focus on the target language, grammar and learner’s role. All of the methods have their strengths and weaknesses and in order to know which method to pick, one must know all the strengths and weaknesses of these methods. In this case study, a teacher from Central Finland was interviewed on her grammar teaching methods and the reasons behind these methods for fifth-graders. Factors influencing her selection of methods were the grammatical topic to be taught, learners’ different learning styles, relevance of the topic and the most natural and authentic situation in which learners’ will be using these grammatical features. She utilizes different methods such as grammar stories, songs and communicative teaching approach. She sometimes teaches grammar explicitly or implicitly depending on her pupils’ levels and on the grammatical topic. Pupils love the grammar stories and would gladly learn grammar. Learners can sometime even be part of the teaching pro cess and in the making of grammar stories. This engages the learners at a deeper level and encourages them to be active in their own learning process.